Examining The Achievement Motivation Of Papuan And West Papuan Students At Universitas Negeri Semarang - Brata, Nugroho Trisnu; Cahyaningtyas, Hana (Universitas Negeri Semarang, 2024)
Students of the Papua Province and West Papua Province through the Affirmation, ADik, and 3T scholarship programs are allowed to continue their education in higher education. Semarang State University (Unnes) is one of the universities that accepts students from the Papua and West Papua Adik programs. This research aims to know the achievement motivation of active Papuan and West Papuan students at Unnes and the learning strategies they apply to increase achievement motivation. The research method used in this study is qualitative, with observation, interviews, and documentation. The results of this study are: 1). The academic motivation of Papuan and West Papuan students in completing their education at Unnes is quite good, it can be seen from their characteristics, namely daring to take moderate risks (middle way) and success is carefully calculated. 2) The learning strategies that Papuan and West Papuan students apply in completing lectures and academic problems are pretty good, where they choose the most appropriate strategy to master the learning material.